2022
DOI: 10.1186/s12879-022-07463-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of pivmecillinam in oral step-down treatment in hospitalised patients with E. coli bacteremic urinary tract infection; a single-arm, uncontrolled treatment study

Abstract: Background The role of oral beta-lactam antibiotics in treating febrile urinary tract infections (UTI) is not yet definite. Today, fluoroquinolones together with trimethoprim–sulfamethoxazole (TMP–MTX) are considered standard of care and often the only available evidence-based oral treatment for febrile UTI. This study clarifies the efficacy and safety of pivmecillinam (PIV) used as step-down therapy for bacteremic urinary tract infection (UTI). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…96 Mecillinam is the active form of the prodrug pivmecillinam and is used to treat lower urinary tract infections. 97 Apart from PBP2, MreB is the most studied protein, and several attempts have been made to search for drugs targeting this protein. However, despite many efforts, no clinically significant drug has been discovered to target the protein due to toxicity issues, while some are still in the initial discovery phase.…”
Section: Antibacterial Drug Targets In the Bacterial Cell Envelopementioning
confidence: 99%
“…96 Mecillinam is the active form of the prodrug pivmecillinam and is used to treat lower urinary tract infections. 97 Apart from PBP2, MreB is the most studied protein, and several attempts have been made to search for drugs targeting this protein. However, despite many efforts, no clinically significant drug has been discovered to target the protein due to toxicity issues, while some are still in the initial discovery phase.…”
Section: Antibacterial Drug Targets In the Bacterial Cell Envelopementioning
confidence: 99%
“…Treating febrile UTI (e.g., pyelonephritis) with pivmecillinam is still controversial due to a lack of evidence from RCTs but is practiced in many institutions in Sweden, Denmark and Norway [ 15 ]. A recent prospective observational study from Norway supported the use of pivmecillinam as step-down therapy for pyelonephritis with E. coli bacteraemia [ 16 ] while a retrospective study of pivmecillinam in EPE-causing pyelonephritis showed high rates of clinical failure [ 17 ]. We believe that these observational studies may reflect a true association, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The common antibiotics that are used for the treatment and management of UTIs include the fluoroquinolones, third generation cephalosporins and other types of beta lactams (Bader et al, 2020). Other novel antibiotics such as pivmecillinam and mecillinam have been used for treatment of UTIs in different setting (Hansen et al, 2022;Jensen et al, 2022). The heavy dependence on the use of antibiotics for the treatment and management of UTI has raised concerns due the emergence of antibiotic resistant bacteria (Haindongo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%